Book review: Code: from information theory to French theory - Marco Schirone (Information Research: An International Electronic Journal)
Geoghegan, Bernard Dionysius. Code: from information theory to French theory. Durham, NC: Duke University Press, 2023. 272 p. ISBN 9781478019008